Fruit and vegetable import duty reduction in Fiji to prevent obesity and non-communicable diseases: a case study. Issue 1 (24th September 2019) - Bell, Colin; Latu, Catherine; Coriakula, Jeremaia; Waqa, Gade; Snowdon, Wendy; Moodie, Marj
Abstract: Objective: To describe the development of Fiji's fruit and vegetable fiscal policies between 2010 and 2014 and explore the impact they have had on import volumes. Design: Qualitative case study and in-depth analysis of policy process. Policy impact was assessed using publicly available import volume data and prices of food products. Setting: Fiji. Participants: Senior government policy makers, non-communicable disease officers from the Ministry of Health and Medical Services (MoHMS) and supermarket managers. Results: In 2011, the Fijian Government introduced an import excise of 10 % on vegetables and reduced the import fiscal duty on fruit that was also grown in Fiji by 10 %. The import tax on vegetables was removed in 2012 in response to a MoHMS request. Policy makers from several sectors supported the MoHMS request, recognized their leadership and acknowledged the importance of collaboration in achieving the removal of the excise. Tariff reductions appear to have contributed to increases in the volume of vegetables (varieties not grown in Fiji) and fruit (varieties grown in Fiji) imported, but it is not clear if this increased population consumption. Conclusions: Reductions in import duties appear to have contributed to increases in volumes of vegetables and fruit imported into Fiji. This case study has demonstrated that governments can use fiscal policy to meet the needs of a range of sectors including health, agriculture and tourism.